Effect of Harvest Season on the Physical Properties, Fatty Acid Composition, and Volatile Compounds of Roasted Cacao Beans - Chumthong, Amornrat; Limjumrern, Nuttarisa; Saensano, Chutikarn; Teerawattanapong, Pornthep; Nualla-ong, Aekkaraj; Rugkong, Adirek; Chiarawipa, Rawee (UI Scholars Hub, 2024)
The prevailing climate is an important factor affecting the development of the physical quality and flavor of cacao (Theobroma cacao L.) beans. The influence of harvest seasons on the physical, chemical, and flavor characteristics of cacao beans from Nakhon Si Thammarat Province, southern Thailand, was assessed. Among cacao beans, those harvested in the rainy season (R) had the highest fresh and dry weights and the lowest bean count per 100 g (87.00 ± 2.83). Although the overall fat content remained relatively constant across harvest seasons, cacao beans harvested in R exhibited a significantly higher fatty acid (C16:0, C18:1, and C18:2) content than those harvested in the dry season (D). Cacao beans harvested in D displayed a more diverse and intense aroma profile than those harvested in R. Therefore, this study proved that harvest seasons significantly influenced the physicochemical characteristics of cacao beans. Cacao beans harvested in D exhibited more complex and distinct postroasting aroma profiles than those harvested in R. Evaluating the seasonal harvesting of cacao beans is crucial for developing cocoa and chocolate with fine and unique flavors in southern Thailand.